Etiological Structure and Features of a Symbiotic Relationship Dominates Agents Acute Intestinal Infections in the North-Eastern Regione of Ukraine - N. G. Malysh; E. V. Holodilo; N. D. Chemych; A. M. Zaritsky (Эпидемиология и вакцинопрофилактика)
The article shows a retrospective epidemiological analysis of the incidence of acute intestinal diseases in 2004 – 2013 in Sumy region. The etiological structure was studied. The properties of Klebsiella pneumoniaе, Enterobacter cloacae, Staphylococcus aureus and Salmonella Enteritidis in a cross-species interaction in populations were studied.It was found, the incidence rates were in the range 159.8 – 193.9 per 100 000 population. The structure of the nosology of acute infectious diarrhea, acute intestinal infection caused by opportunistic pathogens accounted 44.4%. Among the etiologic agents prevailed Klebsiella (28.2 – 34.7%), S. aureus (17.1 – 25.2%) and Enterobacter (12.6 – 18.8%) (p < 0.05). From fecal samples of children were isolated Rotaviruses in 39.5% of cases, adenoviruses – 28.2%, noro-, enteric- and astroviruses respectively – 26.2, 10.4 and 3.2%.It was found the changes in microecological characteristics of intestinal biocenosis in individuals without signs of acute intestinal infection. Association of micro-organisms was characterized by the absence or reduction in the number of representatives of obligate (Bifidobacterium), increasing the number of Enterobacteriaceae, the presence of coliform hemolysing, fungi of the genus Candida, coagulase-negative staphylococci. Among causative agents of diarrhoeal infections K. pneumoniae, E. cloacae and S. Еnteritidis in vitro were revealed indifferent relationships, S. aureus and S. Еnteritidis – synergistic.